(untitled) (Research, Society and Development, 2021)
The objective of this article is to evaluate whether the use of design thinking in corporate environments fosters the development of the skills needed by 21st century professionals. This article can help to encourage the use of design thinking in corporations. Its originality lies in the understanding of the view of professionals who work directly with the approach on the development of professional skills, either by moderating or participating in sessions, or through corporate educational activities that use design thinking as an active teaching methodology. The study involved literature review and field research. The general research methodology was applied, exploratory, field and with a qualitative approach. The data collection included nine semi-structured interviews whose script followed the responsive interview model (Rubin & Rubin, 2011). The data analysis was based on the three codification criteria proposed by Saldaña (2013). The results showed that design thinking promotes the development of the professionals’ personal and social skills when used as an active teaching-learning methodology in corporate educational activities, as well as when resolving conflicts, searching solutions and designing new products and services. Other conclusions are that a fixed mindset might have a negative effect in the development of competencies, and the connection between the content and teaching approach and the real and practical world is essential for the learning and development of the professionals.